Study of the impact of electronic learning tools on the level of formation of health-preserving competence among students of the specialty «therapy and rehabilitation» - Shkola, Olena; Zhamardiy, Valeriy; Donchenko, Viktoriia; Zolochevskyi, Vitalii; Poluliashchenko, Tetiana; Sokolenko, Olena; Pavliuk, Olena (My University, 2023)
Aim: To check the effectiveness of the health-preserving competence formation in future specialists with the processing of multidimensional data using electronic learning tools when studying the discipline «Basics of the theory of health and a healthy lifestyle». Materials and Methods: The research was conducted during the 2022-2023 academic year on the basis of the «Kharkiv Humanitarian and Pedagogical Academy» a communal institution of the Kharkiv Regional Counci, Poltava State Medical University and Luhansk Taras Shevchenko National University. 120 students of the specialty 227 «Therapy and Rehabilitation» and 017 «Physical Culture and Sports» were involved in the pedagogical experiment. Research methods: analysis of scientific and methodical literature; pedagogical observation; pedagogical experiment; pedagogical testing; methods of mathematical statistics. Results: The technology of performing practical competence-oriented tasks and the system of its evaluation, which provided for the diagnosis of the activity component of competence, were substantiated. Test tasks for diagnosing the cognitive component of competence and a special method of processing the results have been developed, which ensures the integration of relevant indicators of individual components of competence into the final generalized result. Conclusions: The diagnostics of the development levels of the formation of the health-preserving components of multidimensional data processing competence among future specialists, the statistical processing of the obtained data at all stages of experimental work, made it possible to make a statistically reliable conclusion about the positive impact of the implemented model of the formation of the studied health-preserving competence by means of electronic learning.
Study of the impact of electronic learning tools on the level of formation of health-preserving competence among students of the specialty «therapy and rehabilitation» / Olena Shkola, Valeriy Zhamardiy, Viktoriia Donchenko, Vitalii Vitalii Zolochevskyi, Tetiana Poluliashchenko, Olena Sokolenko, Olena Pavliuk // Acta Balneologica: Journal of the polish balneology and physical medicine association. Aluna Publishing, 2023. – Vol. LXV, 6 (178). – Р. 406-414
Keywords: health-preservation, competence, model, rehabilitation, higher education students, therapy; здоров'язбереження, компетентність, модель, реабілітація, студенти, терапія